Case report: A rare case of thyrotropin-secreting pituitary macroadenoma with diffuse calcification presenting with hyperthyroidism and literature review - Yan, Huiying; Yan, Chaolong; Mao, Jiannan; Jin, Wei (Frontiers in Oncology, 2023)
Background: Thyroid-stimulating hormone (TSH)-secreting pituitary adenomas (TSHomas) are rare and usually present with hyperthyroidism. Calcification in pituitary tumors is an infrequent finding. Herein, we reported a rare case of TSHoma with diffuse calcification. Case description: A 43-year-old man was admitted to our department with a complaint of palpitations. An endocrinological examination revealed elevated serum levels of TSH, free triiodothyronine (FT3) and free thyroxin, whereas a physical examination revealed no goiter. Computerized tomography (CT) showed a sellar mass with diffuse calcification. Contrast-enhanced T1-weighted images revealed a less enhancing tumor without obvious suprasellar expansion. The tumor was completely removed via an endoscopic transnasal-transsphenoidal surgery. Microscopically, nests of cells were inconspicuous among the diffuse psammoma bodies. Expression of TSH was patchy and only several TSH-positive cells were observed. Postoperatively, the serum levels of TSH, FT3 and FT4 decreased to normal range. Follow-up MR images showed no evidence of residual tumor or regrowth after the resection. Conclusions: Herein, we report a rare case of TSHoma with diffuse calcification that presented with hyperthyroidism. A correct and early diagnosis was made according to the European Thyroid Association guidelines. This tumor was completely removed via an endoscopic transnasal-transsphenoidal surgery (eTSS) and thyroid function was normalized after the operation.